(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The buzz word Vegan products has gained wide popularity in the past few years. Similarly, we can see that many brands have started putting up the cruelty-free label on their products. However, the lack of consumers’ awareness, and the number of companies who still use animal testing methods make this research important. This research paper will analyze the reasons for shift of the consumer’s preference towards vegan and sustainable products. This is an exploratory paper based on primary and secondary research methods. Findings of the research paper provide that though customers are used to buying mass products since ages, there is a change in their buying decisions which will lead to preference towards cleaner and sustainable ethical products. Questionnaire was distributed to 100+ participants across various age groups in Mumbai city. The results show a positive influence of pricing, quick delivery, after-sales service on purchase intention of cosmetic products.